Inhibition of Rac1 activity alleviates PM2.5-induced pulmonary inflammation via the AKT signaling pathway. (August 2019) - Zhang, Shuijuan; Zhang, Weixi; Zeng, Xiaolei; Zhao, Wei; Wang, Zhe; Dong, Xinwei; Jia, Yongliang; Shen, Jian; Chen, Ruijie; Lin, Xixi
Highlights: PM2.5 treatment enhances Rac1 expression in mouse lungs and 16HBE cells. IL-1β level and inflammation were elevated by PM2.5 exposure both in vivo and vitro . Inhibition of Rac1 activity alleviates PM2.5-induced IL-1β release and inflammation. Mechanistically, PM2.5 induced pulmonary inflammation via the Rac1/AKT pathway. Abstract: PM2.5 is the main particulate air pollutant that is capable of inducing airway injury. Previous studies have indicated that Rac1 is involved in cigarette smoke-induced lung inflammation and lipopolysaccharide-mediated pulmonary injury. However, the contribution of Rac1 activity to PM2.5-induced lung inflammation remains largely unclear. Here, we investigated the regulation of Rac1 in PM2.5-induced inflammation in mouse airways and human bronchial epithelial cells (16HBE). The lungs of mice exposed to PM2.5 showed increased IL-1β expression and an accumulation of inflammatory cells, thereby indicating high Rac1 activity. The exposure of 16HBE cells to PM2.5 resulted in elevated Rac1 levels, as well as an increased release of IL-1β. Particularly, the selective inhibition of Rac1 ameliorated the IL-1β release and inflammation in model lungs. Histological assessment showed that treatment with a Rac1 inhibitor, NSC23766, reduced the infiltration of neutrophils and macrophages into the airway lumen. Moreover, the selective inhibition or knockdown of Rac1 decreased IL-1β release in 16HBE cells induced by PM2.5, which correlated with PM2.5-induced Rac1-regulated AKT signaling. Our data suggest an important role for Rac1 in the pathological alterations associated with PM2.5-mediated lung inflammation. Rac1 may be a promising therapeutic target for the treatment of the inflammatory diseases induced by PM2.5 inhalation.